ANALISIS PERTUMBUHAN PENDUDUK KOTA PADANG PROVINSI SUMATERA BARAT TAHUN 2010, 2015, DAN 2019 - Henki Saputra; Khairani khairani (JURNAL BUANA, 2021)
This study aims to determine: 1) The population growth rate in the City of Padang in 2010, 2015, and 2019. 2) the causes that greatly incited the rate of population growth in the City of Padang in 2010, 2015 and 2019. 3) the effect of population growth on availability health, education and economic facilities in the city of Padang. This type of descriptive quantitative research with data analysis techniques using quantitative descriptive. The results showed that: 1) The population growth rate in Padang City in 2010 - 2015 was classified as having a high population growth rate with a birth percentage value of 1.60%, and in 2010-2019 it was classified as having a moderate population growth rate with a birth percentage of 1 , 43%, 2) the aspect that greatly affects the population growth rate in Padang City in 2010, 2015 and 2019 is fertility where the fertility rate continues to increase from 2010, 2015, and 2019, in 2010 the fertility rate was 20, 2015 was 25, and in 2019 it was 27, 3) in 2010 population growth affected the availability of educational facilities, had a strong correlation value with a correlation of 0.616, in 2015 population growth affected the availability of health facilities which had a strong relationship with a correlation of 0.640, and in 2019 population growth has an effect on it p the availability of educational facilities which has a strong relationship with a correlation value of 0.704.